Analisis Yuridis Terhadap Keputusan Hakim Dalam Memutus Perkara Perkawinan Beda Agama di Indonesia Ditinjau Sema No. 2 Tahun 2023 - Pramesti, Novalia Cahyaning Setyo (Media Hukum Indonesia (MHI), 2024)
This research discusses interfaith marriages in Indonesia, which continue to occur despite prohibitions from several religions, especially Islam. Marriage is considered a sacred bond of belief as it relates to the realms of magical and religious thought. Indonesia's diverse society, with various ethnicities, cultures, and religions, leads to interactions between individuals that result in interfaith marriages. The Marriage Law and Constitutional Court decisions have prohibited interfaith marriages. However, such marriages still frequently happen in society, raising concerns about the validity of the marriages, marriage registration, the status of children, divorce, and inheritance issues.The Directorate General of Population and Civil Registration of the Ministry of Home Affairs declares that interfaith marriages are not recognized by the state, except through court rulings and meeting the requirements for changing one's religion. To address these issues, the Supreme Court has issued Circular No. 2 of 2023, providing guidelines for judges to handle applications for registering marriages between individuals of different religions and beliefs to resolve interfaith marriage matters.